Pharmacological and Non-Pharmacological Interventions for Diabetic Neuropathic Pain: Current Evidence and Clinical Applications - Raikwar, Ankita; Panda, Subhranshu; Kumar Posa, Mahesh; Shamsuzzma, Md. (Journal of Neonatal Surgery, 2025)
Background: Diabetic neuropathic pain (DNP) is a common and debilitating complication of diabetes mellitus, primarily resulting from chronic hyperglycemia, induced peripheral nerve damage. It manifests as burning, stabbing, and electric shock-like sensations. This review aims to explore the underlying mechanisms, current management strategies, and emerging therapeutic interventions for DNP. Method: An extensive review of existing literature was conducted to summarize the pathophysiology and treatment approaches for DNP. The study integrates findings from pharmacological and non-pharmacological research, focusing on oxidative stress, neuroinflammation, mitochondrial dysfunction, and impaired neurotrophic signaling as key pathological contributors. Results: Pharmacological therapy remains the mainstay for symptom relief. First-line agents such as duloxetine, pregabalin, and gabapentin demonstrate significant efficacy, while topical treatments like capsaicin and lidocaine patches, along with second-line options including tramadol, tapentadol, and alpha-lipoic acid, provide additional benefit. Non-pharmacological interventions—such as glycemic control, exercise, psychological support, and lifestyle modifications—enhance overall management outcomes. Emerging therapeutic strategies include gene therapy, mesenchymal stem cell (MSC) transplantation, and targeted molecular therapies involving Nav1.7 sodium channel blockers, TRPV1 antagonists, and AT₂R blockers like Olodanrigan. Neuroregenerative approaches using growth factors (NGF, IGF-1, VEGF), along with antioxidant and anti-inflammatory agents (curcumin, resveratrol, N-acetylcysteine), and neuromodulation techniques (spinal cord stimulation, TENS), show promising preclinical and clinical outcomes. Conclusion: Effective management of diabetic neuropathic pain requires a multidisciplinary and personalized approach, combining pharmacological and non-pharmacological therapies. Integration of conventional treatments with novel regenerative and molecular strategies offers significant promise for addressing both symptom relief and disease modification in DNP.